Validity and Reliability of the Malay Version of the Planned Happenstance Career Inventory for Malaysian University Students - Ansarul Haq Tahrir Adli; Mohd Izwan Mahmud; Salleh Amat; Sheerad Sahid; Mohd Azrin Mohd Nasir (Qubahan Academic Journal)
This study aimed to translate and validate the Planned Happenstance Career Inventory (PHCI) for use in a Malaysian context. A total of 500 final-year undergraduate students from four public Malaysian universities participated (100 for Exploratory Factor Analysis, EFA), 400 for Confirmatory Factor Analysis, CFA). Expert review (n=5) established strong face and content validity (0.95). EFA yielded a five-factor structure consistent with the original PHCI: curiosity, risk-taking, persistence, optimism, and flexibility, with all factors demonstrating strong factor loadings (>.6) and explaining 80.276% of the total variance. CFA confirmed the model's goodness-of-fit (RMSEA = 0.070, CFI = 0.943, TLI = 0.935, Chisq/df = 2.950) and demonstrated strong convergent validity and composite reliability. Internal consistency was also excellent, with Cronbach's alpha values ranging from .82 to .90 for the subscales and the total scale. These findings indicate that the Malay version of the PHCI is a valid and reliable instrument for measuring planned happenstance skills among Malaysian university students, offering a valuable tool for researchers and practitioners in this cultural context.